2009
DOI: 10.1007/s00402-009-0918-5
|View full text |Cite
|
Sign up to set email alerts
|

Cocktail therapy for femoral head necrosis of the hip

Abstract: Long-term results are needed to determine whether or not the synergistic effects of ESWT, HBO and alendronate over ESWT alone exist in early hip necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
0
55
0
1
Order By: Relevance
“…Group A consisted of 28 patients (50 hips) who received cocktail therapy, and group B consisted of 35 patients (48 hips) who received only ESWT. After a minimum follow-up of 2 years, the overall results showed 74% improved, 16% unchanged and 10% [13,14].…”
Section: Eswt and Cocktail Therapy For Onfhmentioning
confidence: 91%
See 1 more Smart Citation
“…Group A consisted of 28 patients (50 hips) who received cocktail therapy, and group B consisted of 35 patients (48 hips) who received only ESWT. After a minimum follow-up of 2 years, the overall results showed 74% improved, 16% unchanged and 10% [13,14].…”
Section: Eswt and Cocktail Therapy For Onfhmentioning
confidence: 91%
“…All patients returned to work as healthcare providers and no one required surgical intervention including hip replacement. In a later study of sixty three patients (98 hips) that were randomly divided into two groups for cocktail therapy and ESWT (0.474 mJ/mm 2 energy flux density, 6000 impulses) alone [13]. Group A consisted of 28 patients (50 hips) who received cocktail therapy, and group B consisted of 35 patients (48 hips) who received only ESWT.…”
Section: Eswt and Cocktail Therapy For Onfhmentioning
confidence: 99%
“…They concluded that ESWT is an effective treatment with or without the concurrent use of alendronate. Similarly, Hsu et al [29] have compared the outcomes of ESWT alone and as part of a cocktail treatment consisting of ESWT, hyperbaric oxygen, and alendronate. The authors reported improvement in 79.2% of the patients in the ESWT group, without a significant difference between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapies as well as nonpharmacological therapies, including modified weight bearing, hyperbaric oxygen and extracorporeal shock wave therapy, have been the subject of multiple investigations, including several prospective studies. 18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Bisphosphonates have received specific attention owing to their known effect of decreasing osteoclast-mediated bone turnover that theoretically could prevent subchondral bone collapse. A randomized controlled trial assessing 54 hips reported significantly lower rates of disease progression and need for arthroplasty in patients treated with bisphosphonates for 2 months.…”
Section: Discussionmentioning
confidence: 99%